Funding the PLE Factory in a Multi‐Customer Contract‐Based PLE Organization. Issue 1 (12th May 2021) - Clements, Paul
ABSTRACT: Feature‐based Product Line Engineering is a well‐defined, repeatable, automation‐centric PLE method that is delivering even improvements in time, cost, and quality. An organization intent on adopting it so they can reap the benefits for their product line or product lines needs a viewpoint focusing on the people involved and what they do to keep the PLE factory operational on a day‐to‐day basis. This article describes an organizational structure for Feature‐Based PLE based on the factory concept. It introduces the few roles that have no analog in other development disciplines; they are new to Feature‐Based PLE. It also describes how traditional systems engineering roles carry out traditional systems engineering tasks, but with slight PLE‐inspired extensions. Finally, we will explain why these changes are necessary.